(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Premature Ejaculation is one of the most common causes of male sexual dysfunction with prevalence rate of 20 % to 30% in different studies across the world. Premature ejaculation causes severe anxiety, embarrassment, and depression and relational conflicts. Diagnosing Premature Ejaculation can be problematic due to multidimensional nature of the disease. Premature Ejaculation Diagnostic Tool (PEDT) is a psychometrically valid tool for this purpose. This was a cross-sectional, analytical study and was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. The English version of the PEDT was forward and back translated. An expert committee reviewed the translations and shared their feedbacks and opinions regarding the proposed Bangla questionnaire. Bangla version of Premature Ejaculation Diagnostic Tool was applied to 51 patients after obtaining informed consent. The test was undertaken again after seven days. Validity (Content validity, Face validity, Factor analysis) and reliability (Internal consistency, and test–retest reliability) were assessed. The expert committee expressed their satisfaction regarding Face and Content valid- ity of the questionnaire. Factor Analysis by Principal Component Analysis revealed that the questionnaire had high level of commonalities among the items and yielded a single compo- nent model like the original version. Cronbach’s Alpha () value of 0.827 indicated good level of internal consistency. Intra-class Correlation Coefficient and Spearman’s rho (0.94 and 0.87 respectively) indicated significant correlation between test and retest scores. Results were congruent with findings of similar studies. The Bangla version of PEDT is a valid and reliable scale. It will help to identify patient suffering from premature ejaculation and improve quality of life of the patient and his partner. BSMMU J 2021; 14(4): 132-137